Pelatihan Penyusunan Instrumen Penilaian Keterampilan Menulis Cerita Pendek di SMP Negeri Urumb Merauke - Angla Florensy Sauhenda; Marnina Marnina; Margaretha F Narahawarin (Jurnal Pelayanan Masyarakat, 2025)
This community service program aims to improve teachers' competency in developing short story writing assessment instruments. This is crucial to ensure objective assessments for all students. This community service program contributes to the Indonesian language curriculum, particularly the short story writing curriculum. This community service program was conducted at Urumb State Junior High School in Merauke, with eight teachers participating. The school faced challenges in assessing the lack of objectivity, specifically the use of assessment instruments that align with the learning objectives. Furthermore, students' short story writing skills were still very low. This community service program enabled teachers to develop valid and reliable short story writing assessment instruments. The program took the form of a workshop, which included outreach through training, mentoring, and discussions with the implementation team. During the training phase, the implementation team provided students with an initial understanding of the importance of objective assessment. This was because, in addition to identifying student abilities, teachers could also assess the success of the teaching and learning process in the classroom. During the mentoring phase, the team provided direct guidance to train teachers in developing short story assessment instruments for student assignments. The questions in the assignments are written in language that is easy for students to understand. After developing the assessment instrument, which is the student assignment, a group discussion is held to refine the short story writing assessment instrument. Furthermore, students can improve their short story writing skills through the assignments in the assessment instrument.